Infantile onset Sandhoff disease: clinical manifestation and a novel common mutation in Thai patients - Thipwimol Tim-Aroon; Khunton Wichajarn; Kamornwan Katanyuwong; Pranoot Tanpaiboon; Nithiwat Vatanavicharn; Kullasate Sakpichaisakul; Arthaporn Kongkrapan; Jakris Eu-ahsunthornwattana; Supranee Thongpradit; Kanya Moolsuwan; Nusara Satproedprai; Surakameth Mahasirimongkol; et al. (BMC, 2021)
Abstract Background Sandhoff disease (SD) is an autosomal recessive lysosomal storage disorder, resulting in accumulation of GM2 ganglioside, particular in neuronal cells. The disorder is caused by deficiency of β-hexosaminidase B (HEX-B), due to pathogenic variant of human HEXB gene. Method This study describes clinical features, biochemical, and genetic defects among Thai patients with infantile SD during 2008-2019. Results Five unrelated Thai patients presenting with developmental regression, axial hypotonia, seizures, exaggerated startle response to noise, and macular cherry red spot were confirmed to have infantile SD based on deficient HEX enzyme activities and biallelic variants of the HEXB gene. In addition, an uncommon presenting feature, cardiac defect, was observed in one patient. All the patients died in their early childhood. Plasma total HEX and HEX-B activities were severely deficient. Sequencing analysis of HEXB gene identified two variants including c.1652G>A (p.Cys551Tyr) and a novel variant of c.761T>C (p.Leu254Ser), in 90 and 10% of the mutant alleles found, respectively. The results from in silico analysis using multiple bioinformatics tools were in agreement that the p.Cys551Tyr and the p.Leu254Ser are likely pathogenic variants. Molecular modelling suggested that the Cys551Tyr disrupt disulfide bond, leading to protein destabilization while the Leu254Ser resulted in change of secondary structure from helix to coil and disturbing conformation of the active site of the enzyme. Genome-wide SNP array analysis showed no significant relatedness between the five affected individuals. These two variants were not present in control individuals. The prevalence of infantile SD in Thai population is estimated 1 in 1,458,521 and carrier frequency at 1 in 604. Conclusion The study suggests that SD likely represents the most common subtype of rare infantile GM2 gangliosidosis identified among Thai patients. We firstly described a potential common variant in HEXB in Thai patients with infantile onset SD. The data can aid a rapid molecular confirmation of infantile SD starting with the hotspot variant and the use of expanded carrier testing.